Child Development of Interpersonal Intelligence on Raudhatul Athfal DWP Sunan Kalijaga State Islamic University Yogyakarta - Ulfah, Jamuna (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to determine the role of educators in developing children's interpersonalintelligence and the implementation of children's interpersonal intelligence development at RA UIN Sunan Kalijaga Yogyakarta. The research method used is descriptive qualitative. Theresearch subjects in this study were 1 principal, 4 class teachers and 68 children. The object inthis study is the implementation of guidance and development of children's interpersonalintelligence conducted by educators. Howard Gardner said there are 8 ways you can do toprovoke children's interpersonal intelligence, namely communication, relationships with others, sharing, ownership, caring, compassion, independence, and feelings. All methods have been implemented in RA DWP UIN SUKA Yogyakarta. Educators as public figures for children in schools have an important role in developing interpersonal intelligence in children, namely acting as supervisors, controllers, mentors, advisers / feedback and implement refresh / check again. The implementation of interpersonal intelligence development is carried out through media, direct interaction, the application of PAI learning as an approach and real work / show action as social education, provide a complete explanation of the main objectives of education, prioritize communication in all respects, are felt to have obstacles in the form of the family environment of the students own. The presence of theories about multiple intelligences, is able to open up insights, thoughts and horizons of each person to be more open. Multiple intelligences become lights for everyone to grow, enjoy the process and live their every life story in unique and different ways. Being a rainbow that gives color, for anyone to be able to determine their dreams, ideals, dreams, future and hobbies. Being a vehicle that is ready to take the driver and passengers in any direction you want to go. It is the key to all children in the world that intelligence does not always have to be about books, pens and calculations. And the answer to all the worries that have been imagined about